(untitled) (Iranian Journal of Kidney Diseases, 2019)
Trimethoprim-sulfamethoxazole (TMP/SMX) is a bactericidalantibiotic. The most common adverse effect of TMP/SMX is skinrashes and gastrointestinal symptoms. Although hyperkalemia canoccur with TMP/SMX component but hyponatremia is uncommon. A55- year old woman, known case of rheumatoid arthritis, presentedwith fever and mild dyspnea. According to diagnostic work upthe infection with pneumocystis jirovecii was confirmed. TMP/SMX was started but after 10 days the patient acutely representedwith nausea and became lethargic. The laboratory studies showedmoderate hyperkalemia and severe hyponatremia. TMP/SMX wasstopped and alternative treatment started. Upon discontinuation ofthe drug, serum sodium and potassium levels were both changed tonormal. Hyponatremia as a life threatening adverse effect appearsto be rare with TMP-SMX therapy, but clinicians should be awareof electrolyte disturbances developed with this drug and electrolytemonitoring should always be considered.